Valoración de estrategias competitivas, acuerdos colaborativos y penalizaciones con Opciones Reales Multinomiales y Teoría de Juegos; Valuation of competitive strategies, collaborative agreements and penalties with Multinomial Real Options and Game Theory - Gastón Silverio Milanesi (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– In competitive environments, the design and election of strategies demand considered three potential sources of uncertainty: risks derived from self-actions, risks emerged from states of nature and risks derived from competitor' decisions. The Real Options Theory analyses the first two risks, but doesn't incorporate the uncertainty derived from competitors'actions. For that, the Games Theory must be added to the model. Its develops a numerical model of Games Theory and Multinomial Real Options for value sequential preemption strategies and join venture. In addition, for the agreement a penalty calculator model is developed, an analytic tool for calculating monetary compensations facing contractual defaults. The strategies pure and mixed are selected with Nash equilibrium and valued with multinomial real options model. The theoretical framework exposes the binomial and multinomial model for valuing non correlation technological and markets risk. Also, Game Theory basic elements and resolutions forms are developed. Next, using the cases methodology, the model is applied for valuing preemption and join venture strategies cases. The obtained results are showed in extensive and matrix form. Finally, for inducing cooperative behaviors and agreement s observance, the pecuniary fine valuation is exposed.
Keywords: C71; C72; G13; G32; 330; strategies valuation; multinomial real options; game theory; pre-emption; join venture; penalties valuation